Postimperiaalne sõjapidamine. Ida-Euroopa pärast 1917. aastat [Postimperial Warfare: East and Central Europe after 1917] - Górny, Maciej (Eesti Sõjaajaloo Aastaraamat / Estonian Yearbook of Military History, 2018)
With the failure of the Kerensky-Off ensive the latest, war in East Central Europe acquired a new shape distinct not only from the norms of the Western Front but equally distant from the pre-1916 local situation. The most notable feature of the post-imperial order were new military units, either national or revolutionary, that gradually took over the leading role from imperial armies. The article analyses some basic characteristics of these new armed forces, such as uniforms, provisions, recruitment, rules of conduct and tactics. Special attention is given to the role of railways both in military operations and on the home-front as well as to the phenomenon of the ‚green cadres‘, deserter bands cum peasant armies destabilizing large territories in the wake of independent statehoods in East Central Europe.